APLIKASI JENJANG SOSIAL PENDATAAN KARTU KELUARGA BERBASIS WEB - Martono Martono; Kartika Kartika; Putri Aullia (CCIT Journal, 2017)
The technological advances in the world of information is growing very fast and demanding to stay one step ahead and follow the development of existing ones. We must strive to make innovations in the era of competition is growing rapidly. With all the advantages that exist on the computer is very important for companies or government agencies and the private sector who want to develop and use the power of technology to improve performance. In conducting the data processing activities in order to obtain optimal results. With tersajinya information quickly will speed up the decision-making process, so as to take advantage of the cost, time and energy more effectively and efficiently. In the village of Karang Anyar family card collection system is less accurate and there is a delay of data information. In the family card collection that became the problem is still a lot of people or applicants who still do not understand how the procedure or what is the procedure to be followed by a family card holders. Family card manufacturing process only takes place in the village environment only. Social Study Data Collection Application Family Card is a Web-based application program used to display information about family card data on coral village later and also can facilitate citizens make family cards quickly and accurately